Regional Differences in the Structure of Earnings - Hanushek, Eric A. (The Review of Economics and Statistics, 1973)
T HERE have been a number of attempts to estimate the relationship between schooling and earnings of individuals, but the most common feature of these studies has been severe data limitation which, in turn, has dictated how the analysis could proceed. Perhaps the most serious restriction imposed by the data has been the assumption that earnings relationships are the same across the nation or, at least, across very sizable aggregations of states. This paper examines the viability of such assumptions by looking at differences in earnings functions among smaller, more homogeneous labor markets. This res-earch reveals large differences across labor markets in the returns to human capital and indicates that much of the observed difference in regional and racial earnings results from structural differences in earnings functions.